Direct Reprogramming Improves Cardiac Function and Reverses Fibrosis in Chronic Myocardial Infarction. Issue 3 (12th December 2022) - Tani, Hidenori; Sadahiro, Taketaro; Yamada, Yu; Isomi, Mari; Yamakawa, Hiroyuki; Fujita, Ryo; Abe, Yuto; Akiyama, Tatsuya; Nakano, Koji; Kuze, Yuta; Seki, Masahide; Suzuki, Yutaka; et al.
Abstract : Background: Because adult cardiomyocytes have little regenerative capacity, resident cardiac fibroblasts (CFs) synthesize extracellular matrix after myocardial infarction (MI) to form fibrosis, leading to cardiac dysfunction and heart failure. Therapies that can regenerate the myocardium and reverse fibrosis in chronic MI are lacking. The overexpression of cardiac transcription factors, including Mef2c/Gata4/Tbx5/Hand2 (MGTH), can directly reprogram CFs into induced cardiomyocytes (iCMs) and improve cardiac function under acute MI. However, the ability of in vivo cardiac reprogramming to repair chronic MI with established scars is undetermined. Methods: We generated a novel Tcf21 iCre /reporter/MGTH2A transgenic mouse system in which tamoxifen treatment could induce both MGTH and reporter expression in the resident CFs for cardiac reprogramming and fibroblast lineage tracing. We first tested the efficacy of this transgenic system in vitro and in vivo for acute MI. Next, we analyzed in vivo cardiac reprogramming and fusion events under chronic MI using Tcf21 iCre /Tomato/MGTH2A and Tcf21 iCre /mTmG/MGTH2A mice, respectively. Microarray and single-cell RNA sequencing were performed to determine the mechanism of cardiac repair by in vivo reprogramming. Results: We confirmed the efficacy of transgenic in vitro and in vivo cardiac reprogramming for acute MI. In chronic MI, in vivo cardiac reprogramming converted ≈2% of resident CFs into iCMs, in which a majority of iCMs were generated by means of bona fide cardiac reprogramming rather than by fusion with cardiomyocytes. Cardiac reprogramming significantly improved myocardial contraction and reduced fibrosis in chronic MI. Microarray analyses revealed that the overexpression of MGTH activated cardiac program and concomitantly suppressed fibroblast and inflammatory signatures in chronic MI. Single-cell RNA sequencing demonstrated that resident CFs consisted of 7 subclusters, in which the profibrotic CF population increased under chronic MI. Cardiac reprogramming suppressed fibroblastic gene expression in chronic MI by means of conversion of profibrotic CFs to a quiescent antifibrotic state. MGTH overexpression induced antifibrotic effects partly by suppression of Meox1, a central regulator of fibroblast activation. Conclusions: These results demonstrate that cardiac reprogramming could repair chronic MI by means of myocardial regeneration and reduction of fibrosis. These findings present opportunities for the development of new therapies for chronic MI and heart failure.